TSH RECEPTOR AUTOANTIBODIES - Michalek, Krzysztof (2009)
Thyrotropin receptor autoantibodies (TSHR-Abs) of the stimulating variety are the hallmark of Graves’ disease. The presence of immune defects leading to synthesis of TSHR-Abs causes hyperthyroidism and is associated with other extrathyroidal manifestations. Further characterization of these antibodies has now been made possible by the generation of monoclonal antibodies with this unique stimulating capacity as well as similar TSHR-Abs not associated with hyperthyroidism. Their present classification divides TSHR-Abs into stimulating, blocking (competing with TSH binding) and neutral (no signaling). Recent studies using monoclonal TSHR-Abs has revealed that stimulating and blocking antibodies bind to the receptor using mostly conformational epitopes, whilst neutral antibodies utilize exclusively linear peptides. Subtle differences in epitopes for stimulating and blocking antibodies account for the diversity of their biological actions. Recently non-classical signaling elicited by neutral antibodies has also been described, raising the need for a new classification of TSHR-Abs.